Human aerobic performance: too much ado about limits to O2 - Lindstedt, S. L.; Conley, K. E. (The Journal of Experimental Biology, 2001)
Human endurance performance is often evaluated on the basis of the maximal rate of oxygen uptake during exercise (O2max). Methods for overcoming limits to O2max are touted as means for increasing athletic endurance performance. Here, we argue that the respiratory system is well designed for delivering O2 to meet O2 demands and that no single factor is rate-determining for O2 uptake. We show that O2max can vary 5000-fold among mammals, while any limitation to O2 delivery by a single component of the respiratory system affects O2max by 10% or less. Attempts to increase O2 delivery by enhancing one step in the respiratory system are shown to have little effect. Blood doping, hyperoxia and O2 supplementation of high-altitude natives all raise O2 availability substantially to the working muscles, but these treatments increase O2max only minimally. Finally, we argue that O2 uptake is only one of a number of properties important to human aerobic performance.